The Therapeutic Effects of Goreisan, a Traditional Japanese Herbal Medicine, on Lower-Limb Lymphedema after Lymphadenectomy in Gynecologic Malignancies: A Case Series Study - Yoshikawa, Nobuhisa (Evid Based Complement Alternat Med, 2020)
BACKGROUND: Lower-limb lymphedema (LLL) is a chronic and progressive complication of gynecologic cancer treatment, including pelvic lymphadenectomy. This study aims to investigate the therapeutic effect of goreisan, a traditional Japanese medicine, which has been used for hydrostatic modulation on patients with LLL. METHODS: Patients diagnosed with LLL in our hospital in 2018 were included and principally treated with complex decongestive therapy (CDT), including elastic clothing and lymph drainage. The patients who received a combination therapy of CDT and goreisan (CDT-G group) were prescribed goreisan extract granules, with a dose of 7.5 g per os daily in three doses. Patients who were not prescribed goreisan received CDT alone (CDT group). The severity of lymphedema was evaluated by the estimated limb volume calculated by limb circumferences and the ratio of extracellular water (ECW) to total body water (TBW). RESULTS: Nineteen women with LLL after pelvic lymphadenectomy were included in the study. The number of patients in the CDT and CDT-G groups was 8 and 11, respectively. There were no statistically significant differences between the CDT and CDT-G groups in terms of patient characteristics and severity of LLL before treatment. Reduction in ECW/TBW in the CDT-G group (in the whole body and the affected lower limb) after the intervention was significantly more remarkable than that in the CDT group. CONCLUSIONS: Goreisan-based Japanese herbal therapy may be effective in patients with LLL after retroperitoneal lymphadenectomy.